Universal influenza vaccines: from viruses to nanoparticles - Ye Wang; Lei Deng; Sang-Moo Kang; Bao-Zhong Wang (Taylor & Francis Group, 2018)
Introduction: The current seasonal influenza vaccine confers only limited protection due to waning antibodies or the antigenic shift and drift of major influenza surface antigens. A universal influenza vaccine which induces broad cross-protection against divergent influenza viruses with a comparable or better efficacy to seasonal influenza vaccines against matched strains will negate the need for an annual update of vaccine strains and protect against possible influenza pandemics. Areas covered: In this review, we summarize the recent progress in nanoparticle-based universal influenza vaccine development. We compared the most potent nanoparticle categories, focusing on how they encapsulate conserved influenza epitopes, stimulate the innate and adaptive immune systems, exhibit antigen depot effect, extend the period for antigen-processing and presentation, and exert an intrinsic adjuvant effect on inducing robust immune responses. Expert commentary: The development of an effective universal influenza vaccine is an urgent task. Traditional influenza vaccine approaches are not sufficient for preventing recurrent epidemics or occasional pandemics. Nanoparticles are compatible with different immunogens and immune stimulators and can overcome the intrinsically low immunogenicity of conserved influenza virus antigens. We foresee that an affordable universal influenza vaccine will be available within ten years by integrating nanoparticles with other targeted delivery and controlled release technology.